Perancangan dan Pengembangan Produk Kopi pada UMKM Cening Jaya dengan Model Kano dan Quality Function Deployment (QFD) - Febry Kustriyanto, Kelvin; Emaputra, Andrean; Indri Parwati, Cyrilla (Universitas Muhammadiyah Surabaya Publishing, 2024)
Along with the development of the times, human needs are increasingly developing and complex, these increasing needs are not accompanied by an expansion of existing employment opportunities, QFD is a tool/method used to focus attention on things that are the needs and desires of consumers in preparing service standards. QFD used to capture the voice and desires of customers, then convert them into the right strategy and the products and processes needed. Expectations from customers are translated into specific needs into strategic planning directions and technical actions. The canoe model was made with the aim of categorizing a product or service attribute based on the level of customer satisfaction. The survey was used to obtain information from respondents in the form of attitudes, opinions, or perceptions about an attribute. These attributes will later become the basis for the assessment indicators in determining the steps that must be taken by the company. Data processing using QFD obtains a priority scale that is used to increase customer interest in buying products from UMKM Cening Jaya.